Peran Suami Dalam Menjaga Kestabilan Emosi Istri Pascamelahirkan Di Desa Teupin Batee Kecamatan Idi Rayeuk - SHAFIRA, PUTRI SYAMEILIA (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to understand the role of husbands in maintaining their wives' emotional stability after childbirth in Teupin Batee Village, Idi Rayeuk. The postpartum period is a crucial time with significant physical and emotional changes that can trigger baby blues if not properly addressed. This study uses a descriptive qualitative method with interviews, observations, and documentation of five couples selected through purposive sampling. The results show that emotional support from husbands, such as attention, listening to complaints, creating a comfortable atmosphere, and involvement in child-rearing, has a positive impact on the wife’s emotional stability. However, some husbands are not aware of the importance of this role until they receive education from family members or healthcare providers. Factors influencing husbands' involvement include knowledge, culture, religion, occupation, and emotional management skills. These findings support previous studies that husbands' support reduces the risk of baby blues and improves family harmony.